Direct and indirect control of orexin/hypocretin neurons by glycine receptors. - Karnani, M; Venner, A; Jensen, LT; Fugger, L; Burdakov, D (2011)
Hypothalamic hypocretin/orexin (hcrt/orx) neurons promote arousal and reward seeking, while reduction in their activity has been linked to narcolepsy, obesity and depression. However, the mechanisms influencing the activity of hcrt/orx networks in situ are not fully understood. Here we show that glycine, a neurotransmitter best known for its actions in the brainstem and spinal cord, elicits dose dependent postsynaptic Cl⁻ currents in hcrt/orx cells in acute mouse brain slices. The effect was blocked by the glycine receptor (GLyR) antagonist strychnine and mimicked by the GlyR agonist alanine. Postsynaptic GlyRs on hcrt/orx cells remained functional during both early postnatal and adult periods, and gramicidin-perforated patch-clamp recordings revealed that they progressively switch from excitatory to inhibitory during the first two postnatal weeks. The pharmacological profile of the glycine response suggested that developed hcrt/orx neurons contain α/β-heteromeric GlyRs that lack α2-subunits, whereas α2-subunits, whereas α2-subunits are present in early postnatal hcrt/orx neurons. All postsynaptic currents (PSCs) in developed hcrt/orx cells were blocked by inhibitors of GABA and glutamate receptors, with no evidence of GlyR-mediated PSCs. However, the frequency but not amplitude of miniature PSCs was reduced by strychnine and increased by glycine in ~50% of hcrt/orx neurons. Together, these results provide the first evidence for functional GlyRs in identified hcrt/orx circuits and suggest that the activity of developed hcrt/orx cells is regulated by two GlyR pools: inhibitory extrasynaptic GlyRs located on all hcrt/orx cells and excitatory GlyRs located on presynaptic terminals contacting some hcrt/orx cells.